1997
DOI: 10.1136/jcp.50.8.669
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and inflammation in invasive carcinoma of the breast.

Abstract: Aim-To investigate the relation between angiogenesis and inflammation in invasive carcinoma of the breast. Methods-Sections from 75 invasive carcinomas of the breast were stained using immunohistochemistry for von Willebrand factor, CD3, CD8, CD45RO, CD45RA, CD20, CD68, and c-erbB-2. Tumour vascularity was assessed by counting vessels in the three most vascular areas, and calculating the average (x400 magnification, field 0.168 mm2). Each pattern of inflammation was scored semiquantitatively.Results-The main p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
4
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 27 publications
7
64
4
2
Order By: Relevance
“…Highly necrotic tumours also contained higher levels of focal macrophage infiltration. These results accord well with other previous, albeit only semiquantitative, reports in which simply the presence of necrosis in breast carcinomas was correlated with (1) decreased survival and total vessel counts in highly vascularized tumour areas (Kato et al, 1997) and (2) diffuse tumour infiltration by macrophages (Lee et al, 1997). However, neither of these studies attempted to quantify the actual amount of necrosis present.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Highly necrotic tumours also contained higher levels of focal macrophage infiltration. These results accord well with other previous, albeit only semiquantitative, reports in which simply the presence of necrosis in breast carcinomas was correlated with (1) decreased survival and total vessel counts in highly vascularized tumour areas (Kato et al, 1997) and (2) diffuse tumour infiltration by macrophages (Lee et al, 1997). However, neither of these studies attempted to quantify the actual amount of necrosis present.…”
Section: Discussionsupporting
confidence: 76%
“…However, neither of these studies attempted to quantify the actual amount of necrosis present. Furthermore, Lee et al (1997) only loosely assessed the general level of TAM infiltration per tumour. In the present study, we have used previously published methods to quantify the degree of necrosis as well as the highest density of vessels and macrophages in defined areas of the tumour where 'hotspots' of these cells occur.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to correlate with poor prognosis in carcinomas of the breast (37,38), cervix (39,40), and bladder (41), confirming to some extent the protumorigenic role of macrophages. On the other hand, macrophages in stomach cancer were associated with good prognosis of the disease (42), and there has been varying results with lung cancer (43,44).…”
Section: Discussionmentioning
confidence: 86%
“…Overexpression of macrophage chemoattractants within tumors has been shown to correlate with poor prognosis [67], and the level of macrophage infiltration in tumors is known to be positively correlated with microvessel density, tumor stage, and angiogenesis in human tumors [68]. TAM presence is, therefore, associated with reduced, relapse-free and overall survival [65, 68 -71] in several tumor types (i.e., melanoma [68] and cervical [69,70] and breast [65,71] cancer). Recently, Naldini and co-workers [72] showed that Tie-2-expressing monocytes are a distinct, hemopoietic lineage of proangiogenic cells that account for most of the angiogenic activity of myeloid cells in mouse tumors.…”
Section: Angiostatic Effectsmentioning
confidence: 99%